Using the CLEANED tool in Tunisia to assess the environmental impact of dairy farming - Notenbaert, An Maria Omer; Hoek, Rein van der; Paul, Birthe K.; Frija, Aymen; Tebourb, Ons; Hassan, Sawsan; Masmoudi, Ahlem; Gloy, Nele; Moujahed, Nizar (International Livestock Research Institute, 2024)
In Tunisia, implementing partner ICARDA and its national partners have developed and validated several tools and technologies that align closely with Tunisian government priorities. By doing so, they have provided considerable support to ongoing technical and policy development and implementation. This Brief describes how the Comprehensive Livestock Environmental Assessment for Improved Nutrition, a Secured Environment and Sustainable Development along Livestock and Value Chains (CLEANED) is being used to assess the environmental impact and GHG emissions of dairy farming and has garnered interest for use by the National Agronomic Institute of Tunisia (INAT), and the Office de l’Elevage et des Pâturages (OEP). The Alliance of Bioversity and CIAT and ICARDA collaborated in this work with GIZ. The Alliance guided and enabled GIZ to carry out a CLEANED assessment of dairy systems in Northern and Central Tunisia in 2021.